2017
DOI: 10.1016/j.yjmcc.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1β induces proliferation, survival and paracrine signaling in normal human cardiac ventricular fibroblasts

Abstract: Neuregulin-1β (NRG-1β) is critical for cardiac development and repair, and recombinant forms are currently being assessed as possible therapeutics for systolic heart failure. We previously demonstrated that recombinant NRG-1β reduces cardiac fibrosis in an animal model of cardiac remodeling and heart failure, suggesting that there may be direct effects on cardiac fibroblasts. Here we show that NRG-1β receptors (ErbB2, ErbB3, and ErbB4) are expressed in normal human cardiac ventricular (NHCV) fibroblast cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
(65 reference statements)
0
27
0
Order By: Relevance
“…RNA sequencing (RNA-seq) was performed by Vanderbilt Technologies for Advanced Genomics (VANTAGE) core as previously described [ 39 ], using Illumina TruSeq and HiSeq 3000 (Illumina San Diego, CA, USA)on paired-end-150 flow cell runs at ~32M PF reads per sample. Raw reads (fastq files) were aligned to the mm10 assembly using STAR 2.5.3a and analyzed as previously described using Partek Flow server and Genomics Suite (Partek, Inc, Chesterfield, MO, USA [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA sequencing (RNA-seq) was performed by Vanderbilt Technologies for Advanced Genomics (VANTAGE) core as previously described [ 39 ], using Illumina TruSeq and HiSeq 3000 (Illumina San Diego, CA, USA)on paired-end-150 flow cell runs at ~32M PF reads per sample. Raw reads (fastq files) were aligned to the mm10 assembly using STAR 2.5.3a and analyzed as previously described using Partek Flow server and Genomics Suite (Partek, Inc, Chesterfield, MO, USA [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gel electrophoresis was performed as previously described [ 39 ] and probed with rabbit anti-BDNF (cat. #ARP41970, Aviva Systems Biology Corporation, San Diego, CA, USA) and rabbit anti-GAPDH (cat.…”
Section: Methodsmentioning
confidence: 99%
“…NRG can promote angiogenesis, reverse myocardial remodeling, and improve apoptosis and oxidative stress. It has recently been reported that NRG is also an important signaling protein in the cardiovascular system and in regulating cardiac development and cardiac function, since the tyrosine kinase receptor of NRG (ErbB) has been detected on the surface of cardiomyocytes [ 60 ]. Hedhli et al demonstrated that hypoxia-reoxygenation could induce myocardial endothelial cells to express and release NRG, and that NRG could protect adult mouse cardiomyocytes against apoptosis during hypoxia-reoxygenation [ 61 ].…”
Section: The Beneficial Role Of Cardiokines In Cvdmentioning
confidence: 99%
“…Hedhli et al demonstrated that hypoxia-reoxygenation could induce myocardial endothelial cells to express and release NRG, and that NRG could protect adult mouse cardiomyocytes against apoptosis during hypoxia-reoxygenation [ 61 ]. In addition, NRG may directly improve fibrosis [ 62 ] and induce the production and secretion of IL-1 α and repair factors (like crypto-1), which affect cardiac healing through paracrine signaling [ 60 ]. These findings indicate that endothelium-derived NRG has a protective effect in the ischemic myocardium and it may represent a new therapeutic target for heart diseases.…”
Section: The Beneficial Role Of Cardiokines In Cvdmentioning
confidence: 99%
“…A recent study suggests a potential role of this EGFR ligand in cardiac repair. In human cardiac ventricular fibroblasts, CRIPTO1 production was increased in response to reparative factors, such as NRG1B, and the blockade of PI3K, ERBB2, and ERBB3 by pharmacological inhibitors or neutralizing antibodies significantly reduced CRIPTO1 levels [174]. Currently there are no studies about the role of CRIPTO1 in inflammatory processes or in kidney diseases.…”
Section: Introductionmentioning
confidence: 99%